Diurnal behavior and pairing chronology of the Northern Shoveler wintering in unprotected remnant wetlands of north-eastern Algeria. Issue 1 (2nd January 2017) - Khemis, Mohamed Dhaya El-Hak; Boumaaza, Okba; Bensaci, Ettayib; Amari, Hichem; Boucherit, Khayreddine; Ali, Elafri; Hanane, Saâd; Bouslama, Zihad; Houhamdi, Moussa
Abstract: Although fragmented and semi-permanent wetlands of north-eastern Algeria like a similar wet area around the Mediterranean coast are frequented by a wide range of migratory waterfowl species, they are often considered to be of secondary importance and their functional role is not clearly understood. We studied diurnal time-activity budgets of the Northern Shoveler Anas clypeata during the wintering seasons of 2013–2014 and 2014–2015 in Garaet El-Feïd, a temporary wetland of north-eastern Algeria. Large numbers of this anatid species were regularly observed on the site during the fieldwork (the highest numbers of birds recorded during November and February in the first and second year were 580 and 478 respectively). Recruitment of birds is progressively affected by the hydrological regime; therefore the maximum number of birds was observed when water depth ranged between 60 and 80 cm. In these winter quarter units, the Northern Shoveler spent 63% of its time roosting (including sleeping, resting, and swimming), and 27% feeding. It was found that in both years, in early winter, these ducks spent most of the time resting, in mid-winter –feeding, and in late winter – sleeping. Also, they exhibited unchanged timing of pair formation in both wintering periods ( p = 0.94 under One-sample t -test), the percentage of paired females often peaking in March. In this study we ascertained that wetlands of this category (patchy and semi-permanent) function as roosting and foraging sites for migratory and staging dabbling ducks. This fact should change the prevailing attitude that wetlands of this category are of secondary importance for migratory waterbirds (including the Northern Shoveler) and thus should be useful in reducing their degradation and loss.